2017
DOI: 10.22437/biospecies.v10i1.3480
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh NAA dan BAP terhadap Kultur Jaringan Nenas Tangkit (Ananas comosus (L.) Merr. cv. Tangkit)

Abstract: This study was aimed at investigating the effect of NAA and BAP on the development of basal slip slices in tissue culture of pineapple cv. Tangkit. The experiment was conducted at the Plant Biotechnology Laboratory Agricultural Faculty University of Jambi from July through to October 2016. Six level of NAA concentrations (0, 1, 2, 3 , 4 and 5 mgL-1) were tested in combination with six levels of BAP concentration (0, 1, 2, 3 , 4 and 5 mgL-1). A Completely Randomized Design with 5 replicates was employed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
4
0
6
Order By: Relevance
“…Ikatan rangkap tersebut efektif untuk memacu pertumbuhan tunas dan daun pada eksplan in vitro. Zulkarnain (2009) juga menyatakan bahwa perimbangan konsentrasi auksin dan sitokinin eksogen dengan fitohormon endogen menyebabkan proses fisiologis pada eksplan berlangsung optimal dalam memicu awal pertumbuhan tunas. Setiap sel memiliki respon masing-masing terhadap zat pengatur tumbuh yang diberikan.…”
Section: Pendahuluanunclassified
“…Ikatan rangkap tersebut efektif untuk memacu pertumbuhan tunas dan daun pada eksplan in vitro. Zulkarnain (2009) juga menyatakan bahwa perimbangan konsentrasi auksin dan sitokinin eksogen dengan fitohormon endogen menyebabkan proses fisiologis pada eksplan berlangsung optimal dalam memicu awal pertumbuhan tunas. Setiap sel memiliki respon masing-masing terhadap zat pengatur tumbuh yang diberikan.…”
Section: Pendahuluanunclassified
“…The concentration of sucrose contained in the media had an effect on the growth of the number of roots. The addition of inappropriate PGR tends to cause inhibition of morphogenesis in plants [1]. According to [19] which stated that the results of the analysis on chrysanthemum plants showed that tomato extract also affected the speed of plant root growth, but the control treatment (no addition of tomato extract) gave better root length.…”
Section: Number Of Rootsmentioning
confidence: 99%
“…Tissue culture is a method for separating plant components like cells, tissues, organs and seeds which are then propagated on sterile artificial media so that the plant parts are able to regenerate and differentiate into complete plants [1]. The use of tissue culture is to obtain new plants in large quantities and in a relatively short time and have the exact same physiological and morphological properties as the parent.…”
Section: Introductionmentioning
confidence: 99%
“…Meskipun NAA banyak dilaporkan berperan dalam menginduksi akar (Sesay et al, 2018;Sukmadjaja & Widhiastuti, 2011;Yirssaw et al, 2014), namun dalam penelitian ini kombinasi NAA dengan konsentrasi yang rendah yaitu 0,05 mg L -1 dan BA 0,4 mg L -1 dapat meningkatkan jumlah tunas pada klon Unila UK-1 (Tabel 2) dan jumlah buku pada BW-1 (Tabel 3). Hal serupa terjadi pada tanaman nenas tangkit yang dikulturkan pada media MS dengan NAA 1 mg L -1 yang ditambahkan dengan BAP 2 atau 3 mg L -1 dapat menambah jumlah tunas, tetapi pemberian NAA di atas 3 mg L -1 menghambat pertambahan jumlah tunas meskipun dikombinasikan dengan BAP (Zulkarnain and Neliyati, 2017). Nazir et al, (2022) juga melaporkan pada tanaman obat Valeriana jatamansi bahwa rata-rata panjang tunas tertinggi diperoleh pada media MS dengan NAA 1 mg L -1 dan BAP 2 mg L -1 .…”
Section: Hasil Dan Pembahasanunclassified